Christianity-science compatibility beliefs increase nonreligious individuals' perceptions of Christians' intelligence and scientific ability. (January 2023) - Mackey, Cameron D.; Rios, Kimberly; Cheng, Zhen Hadassah
Nonreligious individuals stereotype Christians as unscientific and see Christianity and science as conflicting. The present studies examined how perceptions of incompatibility between Christianity and science influence nonreligious individuals' stereotypes of Christians in science in the US context. We measured (Study 1) and manipulated (Study 2) participants' beliefs about the compatibility or incompatibility of Christianity and science. In Study 1 ( N  = 365), nonreligious participants ( n  = 214), more so than Christian participants ( n  = 151), perceived Christianity and science as incompatible, which in turn predicted perceptions of Christians as less intelligent and less scientifically able. In Study 2 ( N  = 799; 520 Christians, 279 nonreligious), manipulating perceived Christianity-science compatibility reduced negative perceptions of Christians' scientific ability and general intellect among nonreligious participants. Implications for mitigating negative stereotypes of Christians in science, increasing Christians' representation in scientific fields, and improving relations between Christians and nonreligious groups are discussed.